Służba farmaceutyczna Podkarpacia w latach 1944-2004 na tle przemian prawnych obrotu lekami - Czyż, Lidia Maria (Uniwersytet Rzeszowski, 2016)
Zaopatrzenie farmaceutyczne jako dystrybucja środków leczniczych stosowanych w procesie leczenia pacjenta, to jedno z zadań systemu ochrony zdrowia. Lata 1944 – 2004 w historii zmian administracyjnych obszaru południowo - wschodniej Polski to przedział czasowy, w którym nastąpiły reformy podziału państwa i sposobu zaopatrywania w leki uprawnionych podmiotów gospodarczych. System zaopatrzenia w leki opisano na przykładzie obszaru Podkarpacia, jako zmiany zachodzące w 60-letnim porządku politycznym, od zakończenia II wojny światowej do akcesji Polski do Unii Europejskiej. Praca zawiera definicje prawa farmaceutycznego, także tematy dotyczące organizacji dostaw środków leczniczych do placówek zamkniętej opieki leczniczej i indywidualnego pacjenta oraz obecność w przestrzeni ochrony zdrowia leku jako szczególnego towaru. Przedstawia przebieg tworzenia przepisów prawnych dotyczących kwestii wprowadzania do obrotu środków leczniczych, dystrybucji poprzez apteki ogólnodostępne i systemu odpłatności. W historii zmian dotyczących zaopatrzenia farmaceutycznego w Polsce wyróżnia się trzy okresy: 1944-1950 – funkcjonowanie placówek własności różnych sektorów gospodarczych; 1951-1989 – dominacja własności państwowej; 1989-2004 – powrót do tworzenia zakładów wytwórczych i placówek dystrybucji własności innej niż państwowa. Przedstawiono podstawową literaturę fachową w informacji o leku, omówiono instytucje dopuszczające lek do obrotu.

Provision of pharmaceuticals, defined as distribution of medicinal drugs used in the process of treating a patient, is one of the essential tasks of the health care system functioning in the country. The time from 1944 to 2004, in the history of the administrative changes in south-eastern Poland, was a period during which there were a few significant organizational reforms in subordination of specific types of territorial units and the method of supplying medicinal drugs to all eligible economic entities. The operation of pharmaceutical provisions system has been described based on the example of Podkarpacie, with a focus to changes occurring during the sixty years, in the new political system, from the end of WW II unil the time Poland joined the EU. The theses reviews basic definitions adopted in pharmaceutical law. It looks at various aspects related to the organization of the supply of medicinal products to in-patient healthcare facilities and to individual patients; it also discusses medicinal drug, as a specific preparation subject to trade, and its special place in the sphere of healthcare. It presents the process of making legal regulations related to specific aspects of introducing therapeutic agents into the market. The history of changes related to provision of pharmaceuticals in Poland can be divided into three periods: 1944-1950 – entities involved in trade of pharmaceuticals owned by various sectors of economy; 1951-1989 – domination of state ownership; 1989-2004 – restoration of the possibility to establish both manufacturing and distribution operations owned by entities other than the state. The thesis also presents specialist literature on medicinal drugs as well as institutions responsible for approving medicines for use.
Pharmaceutical service in the Podkarpackie Region during 1944-2004 versus changes in laws related to trade of medicinal drugs
Keywords: Służba farmaceutyczna na tle przemian prawnych; Podkarpacie 1944-2004; Pharmaceutical service versus changes in laws; Podkarpackie Region 1944-2004